Toxicity evaluation of vitex trifoliaethanol extraction using zebrafish (Danio rerio) embryo - Zainal Abidin, Azrina; Segaran Balan, Santhra; Mohamed Ali, Radhiah; Bahari, Hasnah (Universiti Putra Malaysia * Institut Biosains, 2023)
Vitex trifolia (V.trifolia) commonly known as chaste tree and has been proven to have important medicinal benefits in herbal medicine. The aim of this research was to determine the toxicity effect of V.trifolia ethanol extraction on zebrafish embryo (Danio rerio) at different concentrations. Toxicology tests were performed on Danio rerio embryos exposed to V.trifolia extraction at various concentrations from 0.24 to 1000 g/ml for 24, 48, 72, and 96 hours. Observation was done on the survival rate, hatching rate, heartbeat rate, scoliosis rate, and melanin pigmentation formation. Data was analyzed using version 27 of the SPSS. Result shows that the V.trifolia has an LC50 value of 7.681 g/ml. At higher concentrations with the range between 62.5 to 1000 g/ml, no hatching was observed, whereas hatchability of Danio rerio embryos was observed at lower concentrations with the range between 0.244 to 31.25 g/ml. There was no scoliosis observed in any concentration of zebrafish larvae treated with V.trifolia extract. For the heartbeat of Danio rerio embryos, normal heartbeat was obtained at concentration of 0.24 to 31.25 ug/ml up to 96 post fertilization (hpf). However, at 62.5 ug/ml the embryo heartbeat only presence until 24 hpf, followed by zero heartbeat at 48 hpf onwards. Melanin pigmentation was detected at 48, 72, and 96 hpf. In conclusion, the V.trifolia ethanol extraction shows a mild toxicity effect at higher doses when tested on the zebrafish embryo.